Corporate Disclosure, Analyst Forecast Dispersion, and Stock Returns. (January 2019) - Ali, Ashiq; Liu, Mark; Xu, Danielle; Yao, Tong
This article examines whether a corporate disclosure practice is one of the reasons for the forecast dispersion anomaly—the negative relation between analyst forecast dispersion and future stock returns. Prior studies have shown that firms tend to delay the disclosure of bad news and that withholding of news leads to greater dispersion in analysts' forecasts. Accordingly, we predict that firms with higher dispersion in analysts' earnings forecasts are more likely to experience poor earnings in the subsequent quarter, and find evidence consistent with this prediction. After controlling for the relation between forecast dispersion and future earnings, we find that forecast dispersion is no longer significantly negatively related to future stock returns. These results suggest that temporary withholding of bad news by firms increases forecast dispersion among analysts and leads to low subsequent stock returns.